Early Childhood Education and Development in Poor Villages of Indonesia: Strong Foundations, Later Success - Hasan, Amer (World Bank, 2015)
Indonesia has begun to emerge into middle-income status, yet persistent poverty and stark inequalities continue to affect young children?s development. This book tells the story of Indonesia?s efforts to change the trajectory of development for poor children. Many countries have similar aims, but several aspects of what is reported here are especially valuable and perhaps unique.